Total knee and hip arthroplasty in a patient with dwarfism: A report of a patient with a spondylo-epiphyseal dysplasia - (:unkn) unknown (My University, 2006)
In patients with spondylo-epiphyseal dysplasia, coxa vara and genu valgum deformities cause malalignment, which lead to early degenerative changes in hip and knee. It is mandatory to give them a functional replacement for their deformed, painful knees and hips to lead a normal life. We report a patient with inherited dwarfism on whom a replacement of knee and hip was performed. © 2006 Springer-Verlag.
Keywords: Arthroplasty; Dwarfism; Hip; Knee